Porous Surface Films With Tunable Morphologies and Hydrophobic Properties Based on Block Copolymer Under the Effects of Thermal Annealing - Pizarro, Guadalupe del C.; Marambio, Oscar G.; Jeria-Orell, Manuel; Oyarzún, Diego P.; Martin-Trasanco, Rudy; Sánchez, Julio (Frontiers in Chemistry, 2019)
The fabrication of porous-structured polymer films with patterned surface structures has recently attracted increased interest within the material science field. In this work, a series of microstructure scale patterned polymer films were obtained via breath figure methods (BF) with hydrophobic surface films based on self-assembled diblock copolymers by atom-transfer radical polymerization (ATRP). The surface characteristics and morphological properties, pore size, roughness, thickness, and wettability of the block copolymer films was studied in response to variation of the hydrophilic co-monomer structures. A significant improvement of the quality and order of the hydrophobic films was observed in response to thermal annealing and a consequent optimization of the assembly process.